Theory of relaxation parameters of the spectrum shape in the impact approximation–I: General consideration; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 141 - Cherkasov M. R. Mikhail Romanovich (2014, 2014)
Title screen